ANALYSIS OF THE CONE PRESSUREMETER TEST IN CLAY - Houlsby, G; Withers, N (1988)
The cone pressuremeter test is a new in situ test which combines a standard cone penetrometer with a pressuremeter. An analysis of the cone pressuremeter test in clay is presented. The analysis shows that important information about soil properties can be gained from the unloading section of the pressuremeter curve, as well as the loading section. Seven tests using a prototype cone pressuremeter are analysed using the new method, and the derived soil parameters are compared with other tests at the same site. The analysis is shown to fit closely the behaviour observed in the tests, and the derived values of shear modulus and undrained strength agree well with the results of other tests.